Economic well-being and distributional effects of housing-related policies in 3 European countries - Virginia Maestri (University of Essex, Institute for Social and Economic Research (ISER), 2012)
This paper evaluates the redistributive effect of a comprehensive set of housing-related policies, taking into account the housing advantage of homeowners and social tenants. We use the Euromod microsimulation model to simulate housing policies in Estonia, Italy and the United Kingdom. Disentangling the contribution to inequality and poverty of each housing-related policy, we find that the current design of property taxes is not progressive and that other housing policies have a limited impact on inequality in Estonia and on both inequality and relative poverty in Italy. In all three countries, housing-related policies favor the elderly.
Keywords: H23; H53; I38; 330; housing policies; imputed rent; inequality; microsimulation